The Influence of Occupational Health and Safety (OHS) and Work Environment on Employee Performance through Job Satisfaction (Case Study at the Cilincing Motor Vehicle Testing Management Unit) - Dardi Wahyudi; Aang Gunawan; Yana Tatiana; Djamal Subastian; Lira Agusinta (Dinasti Review, 2025)
This study aims to analyze the effect of occupational safety and health (OSH) training on improving the knowledge and performance of vehicle inspection officers at the Motor Vehicle Testing Management Unit (UP PKB) Cilincing, under the Transportation Agency of DKI Jakarta Province. The training provided consists of internal education for new employees as an introductory orientation to enhance their understanding of workplace safety. This research adopts a quantitative approach, with data collected through questionnaires distributed to the entire population of 42 inspection officers. The sampling technique used is non-probability sampling with a saturated sampling method, as all population members were included as the sample. The results show that OSH training has a positive and significant impact on the officers’ work-related knowledge. Furthermore, the increased knowledge gained from the training also contributes to better performance in carrying out vehicle inspections. These findings underscore the importance of OSH training as a managerial strategy to enhance workplace safety and operational efficiency. It is recommended that OSH training be conducted regularly and systematically, not only for new employees but also as a refresher for all officers. Management is also encouraged to develop more interactive and practical training modules to ensure that the acquired knowledge is effectively applied in the field.